2021
DOI: 10.1111/zph.12840
|View full text |Cite
|
Sign up to set email alerts
|

It's our job’: Constraints to investigation of atypical disease events—Opinions of Australian veterinarians

Abstract: Frontline health practitioners need to be adequately prepared to recognize and respond to atypical disease presentations, some of which may have zoonotic potential. Data from previous research have suggested that veterinarians may face challenges in investigation of disease events due to time and money constraints. As part of an Australia‐wide survey project, veterinarians were asked to answer an open‐ended question regarding potential constraints in investigation of atypical disease events where there may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Whilst there is certainly goodwill with regards to further involvement, the capacity for a more structured role is dependent on considerations such as workload and remuneration in particular. The barriers identified in this study are similar to those reported by Steele et al ( 37 ) who list client-related factors, workplace environment and access to external technical support as key impediments to investigations of atypical disease events. Given the identified shortage of both private and government veterinarians in some areas ( 38 , 39 ), many of these may be challenging barriers to overcome without a broader review of the veterinary workforce.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Whilst there is certainly goodwill with regards to further involvement, the capacity for a more structured role is dependent on considerations such as workload and remuneration in particular. The barriers identified in this study are similar to those reported by Steele et al ( 37 ) who list client-related factors, workplace environment and access to external technical support as key impediments to investigations of atypical disease events. Given the identified shortage of both private and government veterinarians in some areas ( 38 , 39 ), many of these may be challenging barriers to overcome without a broader review of the veterinary workforce.…”
Section: Discussionsupporting
confidence: 86%
“…Yeah, I think in a perfect world, people probably would do it for the greater good, but I don't see -yeah, I think that vets commonly do things for the greater good, and absorb the cost, but it does have an impact, particularly when there's drought or when there's other things going on in the community that are impacts on finances. ( 04 are similar to those reported by Steele et al (37) who list client-related factors, workplace environment and access to external technical support as key impediments to investigations of atypical disease events. Given the identified shortage of both private and government veterinarians in some areas (38,39), many of these may be challenging barriers to overcome without a broader review of the veterinary workforce.…”
Section: Resourcing -Time and Financialsupporting
confidence: 87%
“…It is clear from the responses to this survey that C&S testing needs to be a key factor in any approval process. However, previous work has highlighted that disease investigation can be difficult in private veterinary practice because there is no or minimal incentive for clients to fund investigations that are primarily in the public interest [ 70 ]. To ensure equitable and increased access, public funding for approval systems and for diagnostic testing is justified, given the One Health benefits of addressing AMR [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…These arrangements could be expanded to consider a scenario where the primary beneficiary of zoonoses control is the human health sector, through curbing the burden of human disease. Notably, unlike in human medicine, where Australians have access to highly subsidised care through Medicare, costs of veterinary interventions are largely born by animal owners, creating barriers to laboratory investigation 26 . Under a One Health system, costs incurred when ruling out a zoonotic disease or performing culture and sensitivity tests to inform antibiotic prescription in an animal patient could be considered an eligible cost under an expanded Medicare scheme, due to the implications for human health.…”
mentioning
confidence: 99%